Effects of residue management on earthworm cast production after Chromolaena odorata short fallow in the humid tropics - Norgrove, L.; Nkem, J.N.; Hauser, S. (Elsevier, 2003)
We aimed to quantify the relative impact of slashing, mulching, burning and cropping on surface casting by earthworms and whether effects were due to treatments per-se or to the changes in soil temperature and water content they may induce. Surface cast production was monitored during two maize cropping seasons and the subsequent fallow phase. Slashing the vegetation caused a severe decline in surface casting activity, whether or not the plot was cropped afterwards. There was a significant interaction between burning and mulching such that there was significantly lower cast production when mulch was removed by burning than when it was removed by mechanical means. Soil temperature was lower when plots were cropped and mulched but no discernible effects of treatments upon soil water content were found. No correlations were found between surface cast production and soil water content or soil temperature.